Anthology of Arabic Discourse on Translation - Solá Portillo, Sara (TRANS: Revista de Traductología, 2023)
Reseña de Anthology of Arabic Discourse on Translation Tarek Shamma y Myriam Salama-Carr (Eds.) Nueva York, Routledge, 2022, 399 pp.